Characterization of chemical features of potent myeloperoxidase inhibitors. (July 2016) - Soubhye, Jalal; Meyer, Franck; Furtmüller, Paul; Obinger, Christian; Dufrasne, François; Antwerpen, Pierre Van
Background: Despite its important role in the immune system, myeloperoxidase (MPO) is implicated in a wide range of inflammatory syndromes due to its oxidative product HOCl. The oxidative damages caused by MPO make it a new target for developing promising anti-inflammatory agents. In this paper, we tried to understand the mechanism of MPO inhibition in order to facilitate the drug design, to develop more accurate virtual tests and to understand the structure–activity relationship.Results: Based on docking experiments, kinetic studies and in vitro tests, it is determined that a potent MPO inhibitor must possess an oxidizable group in addition to a high affinity with the active site. At last, a new hit was found in this work namely 4-(3-hydroxy-phenoxy)-butylamine (5 ) that has IC50 of 86 nM.Conclusion: Hydroxy-phenoxy alkylamine derivatives were found to be promising MPO inhibitors and they may represent an important starting point in the development of more potent MPO inhibitors. Graphical Abstract: